Pendidikan Kesehatan Berbasis Media Kuartet untuk Meningkatkan Pengetahuan dan Sikap Menggosok Gigi Siswa Sekolah Dasar - Delfi Tika Massau; Emelia Tonapa; Bernadetha Bernadetha (Yayasan Literasi Sains Indonesia, 2025)
Dental and oral health problems in Indonesia remain a serious challenge, particularly among school-aged children. According to the 2023 Indonesian Health Survey (SKI), the national prevalence of decayed, damaged, or painful teeth is 45.6%, and among the 5–9 year age group it reaches 49.9%. In East Kalimantan, the prevalence of dental health problems is 44.8%, with the highest cases occurring in elementary school–aged children. The aim of this study was to analyze the effect of health education using quartet cards on improving toothbrushing knowledge and attitudes among students of MI Ar-Rahmah Loa Janan Ilir. This study employed a pre-experimental design with a one-group pretest–posttest approach. A total of 52 fourth-grade students participated as research samples, selected through proportionate stratified random sampling. The research instrument consisted of knowledge and attitude questionnaires that had been tested for validity and reliability. Data were analyzed using the Wilcoxon test. The results indicated a significant improvement in students’ knowledge and attitudes after receiving health education through quartet cards. The Wilcoxon test produced a p-value of 0.000 (p < 0.05) for both variables, confirming that quartet cards are effective as a learning medium to enhance students’ knowledge and attitudes regarding proper toothbrushing. Quartet cards are therefore effective for use in oral health education to improve students’ knowledge and attitudes toward correct toothbrushing practices. It is recommended that this medium be more widely implemented as an educational method in elementary schools.